First llama (Lama glama) pregnancy obtained after in vitro fertilization and in vitro culture of gametes from live animals - Trasorras, Virginia Luz (2014)
The aim of this study was to evaluate the developmental competence and pregnancy rate of llama hatched blastocysts produced in vitro using gametes from live animals and two different culture conditions. Fifteen adult females were superstimulated with 1500IU of eCG, eleven (73%) responded to the treatment and were used as oocyte donors. Follicular aspiration was conducted by flank laparotomy. Semen collections were performed under general anesthesia by electroejaculation of the male. Sixty-six COCs were recovered from 77 aspirated follicles (86% recovery) and were randomly placed in Fertil-TALP microdroplets with the sperm suspension (20×106live spermatozoa/ml). After 24h, they were placed in SOFaa medium supplemented with FCS and randomly assigned to one of two culture conditions. Culture condition 1 (CC1) consisted of 6 days of culture (n=28) and culture condition 2 (CC2) consisted of renewing the culture medium every 48h (n=35). In CC1, the blastocyst rate was 36% (10/28) and the hatched blastocyst rate was 28% (8/28) whereas in CC2, the blastocyst rate was 34% (12/35) and the hatched blastocyst rate was 20% (7/35) (p>0.05). No pregnancies were obtained after embryo transfer (ET) of CC1 blastocysts (0/8) while one pregnancy was obtained (1/7) after transferring a hatched blastocyst from CC2. Forty-two days after the ET, the pregnancy was lost.This study represents the first report of a pregnancy in the llama after intrauterine transfer of embryos produced by in vitro fertilization using gametes from live animals.